Elevational specialization and the monitoring of the effects of climate change in insects: Beetles in a Brazilian rainforest mountain. (January 2021) - Colares, Carolina; Roza, André S.; Mermudes, José R.M.; Silveira, Luiz F.L.; Khattar, Gabriel; Mayhew, Peter J.; Monteiro, Ricardo F.; Nunes, Maria Fernanda S.Q.C.; Macedo, Margarete V.
Highlights: Narrowly distributed species suggested to monitor climate change in montane forest. Leaf beetles and fireflies as good taxa to search for climate change bioindicators. Malaise trap as a suitable method to monitor climate change beetle bioindicators. Abstract: Mountains have provided important insights on the impacts of climate change on species distribution. Organisms living in tropical mountains are expected to specialize in narrow temperature limits (demonstrating low thermal tolerance), often with narrow elevational distributions relative to temperate species, and may shift their elevational range in response to climate change. Importantly, insects are sensitive, and respond rapidly, to temperature variation, making them suitable bioindicators to monitor the effects of climate change. However, to monitor the effects of climate change in mountains it is important to understand present elevational distribution and other ecological characteristics of local insect populations. In this context, we suggest a method to identify beetle taxa that can be used to monitor climate change effects in tropical mountainous insect species. We illustrate the method by describing the elevational distribution of different beetle groups, associating this distribution with species' thermal range in a tropical mountain forest in Southeast Brazil. Sampling was conducted at Serra dos Órgãos National Park, RJ, Brazil, in the Atlantic Rainforest, one of the main global biodiversity hotspots. In order to systematically sample beetle diversity across elevations, we used flight interception 'Malaise' traps at fifteen different sites, from 130 m to 2170 m a.s.l., over three consecutive months during the rainy season. To investigate species' climatic niches, we recorded climatic variables for this period. We collected 2963 individuals of 272 species, belonging to six Coleoptera groups over a temperature gradient that decreased about 0.5 °C for each 100 m in elevation. Considering the thermal tolerance of species from tropical mountains and their narrow elevational range and abundance, five Coleoptera species belonging to Cerambycidae, Eumolpinae (Chrysomelidae), Lampyridae and Phengodidae were considered suitable bioindicators, and the Eumolpinae and Lampyridae were the ones with the narrowest elevational range. We suggest that the use of abundant species (or groups of species) with narrow elevational range as bioindicators can be valuable to monitor the effects of climate change on the biota, allowing us to evaluate how species are responding to changes over time.